-8x-6=-2x-60

Simple and best practice solution for -8x-6=-2x-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-6=-2x-60 equation:


-8x-6=-2x-60

We simplify the equation to the form, which is simple to understand
-8x-6=-2x-60

We move all terms containing x to the left and all other terms to the right.
-8x+2x=-60+6

We simplify left and right side of the equation.
-6x=-54

We divide both sides of the equation by -6 to get x.
x=9

See similar equations:

| -n=1/3^-5 | | (x^2-4x-2)x(x+7)= | | 3(2p+3q)+-4q= | | -7x-6=-12x-41 | | -n=1/4^-4 | | (x^2-4x-2)(x+7)= | | -n=1/9^-2 | | -14x+6=-6x+38 | | -14x+6=-6+38 | | 3x-2=-4x+33 | | 17x-2=8x+88 | | -n=1/5^-5 | | 9y-1=-10+12y | | -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p | | -x/3+58= | | -3b=-12 | | 2b+3(b-2)=4 | | -14n+4=-13n-17 | | -8w^2-8w+19=0 |

Equations solver categories